A cross-sectional study determining the relationship between eating and drinking skills and functional independence levels of patients with cerebral palsy: Eating and drinking function in children with CP - Sirzai , Hulya; Dundar , Emine Ahi (Journal of Surgery and Medicine, 2022)
Background/Aim: In cerebral palsy (CP), drinking/eating disorders are considered common. To evaluate these disorders, a very detailed and lengthy evaluation is required. Few tools are available to identify children who need to be evaluated. This study determined whether the functional independence level of children with CP is sufficient to predict their drinking/eating skills and to determine the relationship between this functional level and these skills. Methods: A total of 105 children with CP aged 4–8 years participated in a cross-sectional study in our outpatient clinic. Functional classification was assigned using the Gross Motor Function Classification System and Manuel Ability Classification System (GMFCS and MACS, respectively). For a functional assessment of daily life, the Pediatric Evaluation of Disability Inventory (PEDI) was performed by asking a relative of the child. The Eating and Drinking Abilities Classification System (EDACS) level was added to the study after asking the caregivers of the patients for eating/drinking evaluations. Results: According to the current results, we found a negative correlation between EDACS and PEDI scores. As the EDACS grade increased, the PEDI subscale and total scores decreased in a statistically significant manner (P < 0.001), while the GMFCS and MACS scale increased statistically (P < 0.001). As the PEDI subscale and total scores increased, the levels of GMFCS and MACS decreased statistically significantly (P < 0.001). Conclusions: The performances of children with CP in terms of activities of daily living are closely related to their performance in eating/drinking activities. If children are independent in their mobility, social functions, and daily self-care, they are also more independent in terms of eating/drinking.